Analisis Perkembangan Komunikasi Demokrasi di Era Reformasi Dengan Prinsip-Prinsip Masyarakat Berdemokrasi dan Negara Hukum Sesuai Undang-Undang Dasar Republik Indonesia 1945 - Triadi, Irwan; Fiandie, Ursula Jacqueline (Media Hukum Indonesia (MHI), 2024)
This research aims to highlight and classify differences in communication styles as an indication of the orderly and free functioning of democracy in accordance with the principles of democracy and the rule of law according to Constitutional Law experts. The research method used is a normative juridical method by linking the principles of the 1945 Constitution and the doctrines of experts that are in line with the topic of discussion. The research method used by the author is a normative juridical method. The normative juridical research method involves legal research carried out through library research, where the main material to be analyzed is collected by searching for regulations and literature related to the problem being studied. The normative juridical method is used by observing and processing the process of implementing ideal democracy in national and state life. As a country that upholds the principles of democracy, freedom to express opinions has been the right of the Indonesian people since the time we succeeded in winning national independence. Even though freedom of opinion is something that is an indicator of the functioning of democracy in a country, it is important to remember that freedom of opinion must also pay attention to ethics and morals in its delivery. The concept of freedom of opinion must comply with Pancasila democracy.